Ion induced field effect in silicon in nematic liquid crystal cell - Kucheev, S.I.; Gritsenko, M.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
An influence of ion charge on surface conductivity of silicon in In₂O₃/5CB/monocrystal silicon/Al structure, in which a specific resistance of silicon is much less than a specific resistance of liquid crystal layer, was studied. Within the frequency range of 103-106 Hz of external voltage, a depletion state in silicon has been observed. We found that the field effect in silicon is induced by ion charges localized near silicon surface. It is shown that method based on visualization of n+ pockets on n-Si substrate by liquid crystal enables to estimate the impurity ion density near silicon surface. Analysis of the field effect induced by polarized charges formed by the prior action of DC voltage has allowed us to conclude that: 1) up to several volts of DC, a charge injection from silicon surface into liquid crystal is absent; 2) ion charge accumulated near silicon surface is partially adsorbed on silicon surface; 3) high voltage with "+" U polarity on silicon causes full absence of photosensitivity. We demonstrated that such type of structure could be used as liquid crystal spatial light modulator.